Penyuluhan Mekanisme Pengendalian Pemanfaatan Ruang Wilayah Kota di Kantor Kecamatan Biringkanaya Kota Makassar - Arifuddin Akil (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2020)
Various conditions that cause irregularities in spatial planning implementation are a result of negligence in planning, spatial use, and controlling land utilization. Specifically, land utilization control is a strategic task of the government in realizing the spatial expectations, but in the field application there are still problems such as irregularities in land utilization and poor public knowledge. The basic assumption of the problem, especially in Biringkanaya District, is the lack of understanding of the apparatus to carry out the task of fostering the community and controlling land utilization in accordance with regulations. This problem can be overcome according to the target of this activity through increasing the apparatus knowledge related to the problem. Therefore this activity aims to increase the knowledge and insight (capacity building) of government officials regarding the substance of the land utilization problem. The method used in accordance with the targets and objectives of this activity is to educate government officials, especially at the Biringkanaya District level with the agenda of presenting: 1) regulatory material concerning guidance to the public so that they can play an active role in spatial planning, 2) material on regulation and substance of controlling land utilization, and 3) material on the mechanism of controlling land utilization in accordance with Permendagri No.115 of 2017. The results of the activities implementation show an increase in participant's knowledge regarding the spatial planning development of the community, as well as understanding regulations, substance and mechanism of controlling the land utilization in the region. In the discussion it was revealed that the problems in the field were not yet optimal due to the limited knowledge of the apparatus regarding the development and control of land utilization. Some regulation of land utilization, have not been mastered due to limited information to the apparatus at the sub-District level.